Nanotechnology: Current applications and future scope in food - Monalisa Sahoo; Siddharth Vishwakarma; Chirasmita Panigrahi; Jayant Kumar (Food Frontiers, 2021)
Abstract Nanotechnology is the new frontier in the transformation of conventional agriculture and food sector into an emerging form for development of food industry. Innovations in nanofood, nanosensors, nanopackaging, nanofertilizers, and nanopesticides are the major recent advancements of nanoscience and technology. Nanoscience‐based technology has a vibrant impact on food quality, food safety, and food packaging aspects including nanofood drug delivery, nanonutraceuticals, and functional food. Application of nanotechnology facilitates food preservation, nutrition enhancement, and safe delivery of micronutrients and bioactive components. Recent trends and advancement of nanotechnology and its promising opportunities and challenges in food processing sector are discussed in this review. Synthesis of nano material and their application to food sectors with concerned health regulatory and risk assessment issues are addressed. Although nanotechnology is a promising prospect and has advancement application in food industry, still efforts are required for intensive research in nanofood system and creating public consumer awareness.